Effect of Time-Dependent Pinning Pressure on Abnormal Grain Growth: Phase Field Simulation - Kim, Jeong Min; Min, Guensik; Shim, Jae-Hyeok; Lee, Kyung Jong (KOREAN INST METALS MATERIALS, 2018)
The effect of the time-dependent pinning pressure of precipitates on abnormal grain growth has been investigated by multiphase field simulation with a simple precipitation model. The application of constant pinning pressure is problematic because it always induces abnormal grain growth or no grain growth, which is not reasonable considering the real situation. To produce time-dependent pinning pressure, both precipitation kinetics and precipitate coarsening kinetics have been considered with two rates: slow and fast. The results show that abnormal grain growth is suppressed at the slow precipitation rate. At the slow precipitation rate, the overall grain growth caused by the low pinning pressure in the early stage indeed plays a role in preventing abnormal grain growth by reducing the mobility advantage of abnormal grains. In addition, the fast precipitate coarsening rate tends to more quickly transform abnormal grain growth into normal grain growth by inducing the active growth of grains adjacent to the abnormal grains in the early stage. Therefore, the present study demonstrates that the time dependence of the pinning pressure of precipitates is a critical factor that determines the grain growth mode.
Keywords: MICROALLOYED STEELS; STATIC RECRYSTALLIZATION; PRECIPITATION KINETICS; MODEL; AUSTENITE; MICROSTRUCTURE; PARTICLES; EVOLUTION; SIZE